Population and autecology of the endangered Rafflesia meijeri in Batang Gadis National Park, Indonesia - RIDAHATI RAMBEY; NIRWAN SAPUTRA; IFHAM FUADI RAMBE; BOBBY NOPANDRY; SYAHDIN ZUNAIDI; EVO LORIVA CHRISTY; TEGUH SETIAWAN; YUNUS AFIFUDDIN; ADRIAN HARTANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Rambey R, Saputra N, Rambe IF, Nopandry B, Zunaidi S, Christy EL, Setiawan T, Afifuddin Y, Hartanto A. 2023. Population and autecology of the endangered Rafflesia meijeri in Batang Gadis National Park, Indonesia. Biodiversitas 24: 1845-1852. Indonesia is renowned for its tropical forests, which harbor high biodiversity. One of the notable flora found in the Indonesian forest is the holoparasitic plant Rafflesia, which attaches to its host, Tetrastigma spp. Among the 30 species of Rafflesia, 11 species have geographical distribution in Indonesia, specifically in Sumatra, Java, and Kalimantan. Rafflesia is listed as Endangered by the IUCN Red List, highlighting the conservation importance of this plant group. The objective of this study was to determine the number of individuals, ecological conditions, and structure of plant species composition in the habitat of Rafflesia meijeri Wiriad. & Sari in two localities (i.e. Sopotinjak and Pagar Gunung) in Batang Gadis National Park. Population and autecology data of R. meijeri were collected using the nested plot method and the vegetation community was analyzed in terms of the Importance Value Index (IVI), biodiversity and richness indices. The results of the study indicated that in Sopotinjak there was one individual of R. meijeri in the bract phase, two individuals in the ruptured copule phase, and 13 individuals in the round copule phase. In Pagar Gunung, there were 19 individuals in the late blooming phase, seven individuals were in the bract phase, three individuals were in the copule phase, and two individuals were in the ruptured copule phase. Species with the highest IVI in the vegetation community around the habitat of R. meijeri from seedling, sapling, pole to tree level in Pagar Gunung were Litsea firma (Blume) Hook.fil., Eugenia pyriformis Cambess., Cinnamomum burmanni (Nees & T.Nees) Blume, and Castanopsis javanica (Blume) A.DC., respectively. Species that were significantly associated with R. meijeri in Sopotinjak were Kyllinga brevifolia, Melastoma malabathricum L., Calamus paspalanthus Becc, Calamus rotang L., and Gliricidia sepium (Jacq.) Kunth. The discovery of nine specimens of the host plant Tetrastigma papillosum (Blume) Planch. in Pagar Gunung and Sopotinjak indicates the importance conservation efforts aimed at conserving R. meijeri, as well as the flora and habitats that are intricately linked to it.